37 Automated Laboratories: When Technology Needs a Human Touch. (11th January 2018) - Forest, Stefanie; Vossoughi, Sarah; Connelly, Charles; Kratz, Alexander; Stotler, Brie
Abstract: The technological revolution has changed the field of laboratory medicine with a shift from manual specimen processing to automation. Many laboratories have transitioned to robotic processing for high throughput testing in an effort to enhance workflow, improve efficiency, decrease turnaround time (TAT), and maximize resource utilization. This is beneficial for patient care and client satisfaction, and advantageous in a field of diminishing resources and skilled personnel shortages. This study analyzed the TAT for troponin testing before and after implementation of an automated laboratory at an academic medical center. Data collected included the monthly troponin TAT (reported as the time interval that 90% of samples are complete from receipt in lab to result time), and the number of troponin tests performed by the laboratory from 2015 to 2016. The medical center transitioned from Abbott ARCHITECT ( i 2000SR, i 1000SR ) analyzers (North Chicago, IL) manually loaded and operated by medical technologists to the Roche cobas 8000 modular analyzer series with a modular preanalytic (MPA) system in November 2015. The MPA scans the specimen barcodes, downloads the assay requests, centrifuges the samples, aliquots them (if necessary), and triages to the appropriate analyzer using a robotic track. The TAT increased from 43.3 minutes in October 2015 (preautomation) to 113.3 minutes in November 2015 (postautomation), peaking in January 2016 at 147.5 minutes. The TAT remained above 100 minutes until a system change was implemented at the end of June 2016. The overall troponin test volume did not increase after implementation of the automated laboratory. The increase in TAT was caused by an inability to triage troponin specimens prior to being placed on the MPA and a longer than expected wait time for centrifugation once loaded on the MPA. The troponin assay and many other assays were performed using serum separator tubes, and the new system allowed multiple assays to share a tube. Therefore, no visual triage was possible for specimens with a troponin order; hence, these specimens were not preferentially loaded onto the MPA. While the troponin assay was the first test performed if other assays shared the tube, the time spent in queue was a significant delay factor. To mitigate the problem, the specimen tube for the troponin assay was changed from a serum separator tube to a designated lithium heparin tube (green top) that was only used for troponin assays. The green top was a visual signal for immediate loading onto the MPA. This helped decrease the TAT to 70.5 minutes the month after implementation with a continued downward trend to a nadir of 67.3 minutes in December 2016. The laboratory is considering the purchase of additional instrumentation to decrease TAT further. This study describes an unexpected pitfall of automation and highlights the importance of a thorough workflow assessment.